Novel OCRL mutations in patients with Dent-2 disease - Böckenhauer, Detlef; Bökenkamp, Arend; Nuutinen, Matti; Unwin, Robert; van't Hoff, William; Sirimanna, Tony; Vrljicak, Kristina; Ludwig, Michael (Journal of Pediatric Genetics, 2012)
Dent disease is an X-linked tubulopathy frequently caused by mutations in the CLCN5 gene encoding the voltage-gated chloride channel and chloride/proton antiporter, ClC-5. About 15% of patients with a Dent' phenotype have mutations in the OCRL gene, which also causes Lowe oculocerebrorenal syndrome. To distinguish these patients from the more severe Lowe phenotype, they are diagnosed as having Dent-2 disease. We studied 14 CLCN5-negative patients from 12 families with a phenotype resembling Dent disease for defects in OCRL. In six of these kindreds three novel (c.149+1G>A, c.1126A>T, c.1547T>C) and three repeatedly observed mutations (c.166_167delTT, c.901C>T, c.1426C>T) were discovered. With the exception of a lower prevalence of nephrocalcinosis, the renal phenotype is identical with patients harboring a CLCN5 mutation. Affected children may have some of the extra-renal symptoms of Lowe syndrome, such as peripheral cataracts, mental impairment, stunted growth or elevation of creatine kinase/lactate dehydrogenase, blurring the distinction between those two clinical entities.
Keywords: Dent-2 disease; OCRL gene; proximal tubulopathy; cataracts; mental retardation